2013
DOI: 10.1021/ml400040v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Characterization of Two Novel, Brain Penetrating P2X7 Antagonists

Abstract: The synthesis and preclinical characterization of two novel, brain penetrating P2X7 compounds will be described. Both compounds are shown to be high potency P2X7 antagonists in human, rat, and mouse cell lines and both were shown to have high brain concentrations and robust receptor occupancy in rat. Compound 7 is of particular interest as a probe compound for the preclinical assessment of P2X7 blockade in animal models of neuro-inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 16 publications
2
36
0
Order By: Relevance
“…Kim et al (2013) have shown, however, that αS oligomers spontaneously secreted by a neuroblastoma cell line had the potential to activate TLR-2 in microglial cells whereas fibrils produced from recombinant αS were unable to do so. Glutamate release induced by αSa was also significantly curtailed by JNJ, a synthetic antagonist for purinergic P2X7 receptors (Letavic et al, 2013), which is reminiscent to previous studies showing that oligomeric forms of αS bind directly to this receptor subtype . Glutamate release induced by αSa was also significantly curtailed by JNJ, a synthetic antagonist for purinergic P2X7 receptors (Letavic et al, 2013), which is reminiscent to previous studies showing that oligomeric forms of αS bind directly to this receptor subtype .…”
Section: αSa-mediated Glutamate Release In Microglial Cells Is Medisupporting
confidence: 67%
See 2 more Smart Citations
“…Kim et al (2013) have shown, however, that αS oligomers spontaneously secreted by a neuroblastoma cell line had the potential to activate TLR-2 in microglial cells whereas fibrils produced from recombinant αS were unable to do so. Glutamate release induced by αSa was also significantly curtailed by JNJ, a synthetic antagonist for purinergic P2X7 receptors (Letavic et al, 2013), which is reminiscent to previous studies showing that oligomeric forms of αS bind directly to this receptor subtype . Glutamate release induced by αSa was also significantly curtailed by JNJ, a synthetic antagonist for purinergic P2X7 receptors (Letavic et al, 2013), which is reminiscent to previous studies showing that oligomeric forms of αS bind directly to this receptor subtype .…”
Section: αSa-mediated Glutamate Release In Microglial Cells Is Medisupporting
confidence: 67%
“…In the same setting, we also tested the impact of JNJ (20 μM), a synthetic antagonist for purinergic P2X7 receptors (Letavic et al, 2013). To address this point, microglial cells were exposed to αSa (70 μg/ml) in the presence or not of MAb mTLR2 (2.5 μg/ml), an antagonistic antibody for TLR2 receptors (Chen, Xie, Turkson, & Zhuang, 2015).…”
Section: αSa Stimulate Glutamate Release In Microglial Cells Througmentioning
confidence: 99%
See 1 more Smart Citation
“…These newer druglike antagonists are particularly important for the purinergic field, because the first generation of antagonists was generally designed for in vitro, rather than therapeutic, use. Furthermore, many of the original antagonists are subject to degradation when used in vivo or are predicted to have poor pharmacokinetics (Friedle et al, 2010;Jiang, 2012) , and N-(adamantan-1-ylmethyl)-5-[(3R-amino-pyrrolidin-1-yl)methyl]-2-chloro-benzamide (AACBA; also known as GSK314181) (Broom et al, 2008), the cyanoguanidine derivative (Honore et al, 2006), the cyclic imide 3- [1-[[(39-nitro[1,19-biphenyl]-4-yl)oxy]methyl]-3-(4-pyridinyl) propyl]-2,4-thiazolidinedione (AZ11645373) (Stokes et al, 2006), and the nicotinamide derivative N-([4-(4-phenyl-piperazin-1-yl]tetrahydro-2H-pyran-4-yl)-methyl)-2-(phenyl-thio) nicotinamide (JNJ-47965567) (Letavic et al, 2013). The concentration responses of some of these specific antagonists (including A438079 and AZ11645373) have been determined at native murine P2X7 receptors Pupovac et al, 2013b), which is useful for their in vivo application.…”
Section: Modulators Of P2x7 Receptor Activationmentioning
confidence: 99%
“…These structures indicate that the P2X7 receptor tolerates very bulky residues, like cycloheptyl, adamantyl and related ring systems. Several other P2X7 antagonists that penetrate well into the brain have recently been described, including GSK1482160 ( 146 ), which has been prepared in 11 C-labeled form to provide a ligand for positron emission tomography (PET) studies (Gao et al, 2015), JNJ-47865567 ( 147 ) (Letavic et al, 2013; Bhattacharya et al, 2013), JNJ-42253432 ( 148 ) (Lord et al, 2014) and the triazolopyrazinylmethanone 149 (Rudolph et al, 2015). A novel, useful 3H-labeled antagonist radioligand, [ 3 H]JNJ-54232334 ( 150 ) has been reported (Lord et al, 2015).…”
Section: P2xr Modulatorsmentioning
confidence: 99%